The Separate Physics and Dynamics Experiment (SPADE) framework for determining resolution awareness: A case study of microphysics. Issue 16 (29th August 2013) - Gustafson, William I.; Ma, Po‐Lun; Xiao, Heng; Singh, Balwinder; Rasch, Philip J.; Fast, Jerome D.
Abstract : [1] Multiresolution dynamical cores for weather and climate modeling are pushing the atmospheric community toward developing scale aware or, more specifically, resolution aware parameterizations that function properly across a range of grid spacings. Determining resolution dependence of specific model parameterizations is difficult due to resolution dependencies in many model components. This study presents the Separate Physics and Dynamics Experiment (SPADE) framework for isolating resolution dependent behavior of specific parameterizations without conflating resolution dependencies from other portions of the model. To demonstrate SPADE, the resolution dependence of the Morrison microphysics, from the Weather Research and Forecasting model, and the Morrison‐Gettelman microphysics, from the Community Atmosphere Model, are compared for grid spacings spanning the cloud modeling gray zone. It is shown that the Morrison scheme has stronger resolution dependence than Morrison‐Gettelman, and the partial cloud fraction capability of Morrison‐Gettelman is not the primary reason for this difference. Key Points: The SPADE framework allows targeted resolution testing of parameterizations. Microphysics parameterizations are not inherently resolution independent. Morrison microphysics is more resolution dependent than Morrison‐Gettelman.